Ecofisiologia do tomateiro e qualidade pós-colheita do tomate cereja sob fertirrigação com efluente da piscicultura em diferentes fases fenológicas - Silva, Alex Álvares da (2019)
The scarcity of good surface quality water and the low natural fertility of the soils are limiting factors of the agricultural production practiced in the semiarid region of Brazilian northeast. Thus, alternative sources of water resources and fertilizers for agriculture have been sought, such as the shrimp and fish farming effluents. An alternative for disposal and treatment of this waste is its use as a source of water and organic matter for fertilization of crops, revegetation of degraded areas, etc. However, the use of these residues requires the adoption of well-defined parameters regarding the application of effluent volume as a function of the cultivated plant species, as well as the prediction of environmental cases. In this context, the objective was to evaluate fish farming effluent as a water source for cherry tomatoes (Solanum lycopersicon, cv. Fern) under different management strategies in the use of fish farming effluent at different phenological stages. A greenhouse experiment, using 4 dm3 capacity polyethylene bags filled with homogenized coconut fiber and organic compound (2: 1), using a randomized block design with 10 treatments and 4 replications. The treatments consisted of the use of piscicultural effluent (R) with electrical conductivity (EC) = 4.54 dS m-1 and EC supply water (A) = 0.54 dS m-1, interspersed during four phenological phases ( growth from 0 to 19 days after transplantation – DAT), flowering from 20 to 31 DAT, fruit filling from 32 to 60 DAT and ripening from 61 to 77 DAT). We assessed growth (height, stem diameter and leaf number) at 24 and 56 DAT, gas exchange (CO2 assimilation rate, transpiration, stomatal conductance, internal CO2 concentration, instantaneous carboxylation efficiency, instantaneous use efficiency) water, leaf blade temperature) at 54 DAT, chlorophyll A fluorescence, photosystem II quantum efficiency, electron transport rate, photochemical extinction coefficient at 54 DAT, chloroplast pigments and electrolyte leakage at 75 DAT, production (number e average fruit weight per plant and bunch, number and average weight of bunch per plant) and postharvest quality (longitudinal and transverse diameter, vitamin C, soluble solids, titratable acidity, hydrogen potential and flesh firmness). The results of the analysis indicate fish culture effluent may be used as a water and nutritional source in the cultivation of cherry tomatoes with minimal yield losses. When applied in the flowering phase, the effluent caused a reduction in average weight and increased fruit acidity. The use of effluent promoted higher photosynthetic activity, water use efficiency and soluble solids content, being therefore indicated for the cultivation of cherry tomatoes in substrate. The use of fish farming effluent enables better use of water resources and agricultural inputs, making it even better to preserve the extensively exploited natural resources, conserving good quality water for other uses